PENGARUH LEVERAGE, PRICE EARNING RATIO, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LOGAM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Iin Indarti; Nurdhiana Nurdhiana (Dinamika Akuntansi Keuangan dan Perbankan, 2021)
The determinants of firm value in this study are the influence of leverage, price earning ratio and profitability. The sample in this study amounted to 45 data from 15 companies listed on the Indonesia Stock Exchange 2017-2019 period. This type of research is quantitative research and the data analysis technique used is multiple linear regression analysis which is used to determine the effect of each independent variable on firm value. Based on the partial test (t test) Leverage variables, price earning ratio and profitability have no effect on firm value. The coefficient of determination in this study is 15%, which means, Leverage, Price Earning Ratio and Profitability on Firm Value in Metal Companies Listed on the Indonesia Stock Exchange for the 2017-2019 period have an influence on firm value by 15%. And the rest is influenced by other variables outside of this study. Keywords: leverage, price earning ratio, profitability, firm value